Fostering Special Education Certification through Professional Development, Learning Communities and Mentorship - Trahan, Mitzi P.; Olivier, Dianne F.; Wadsworth, Donna E. (Journal of the American Academy of Special Education Professionals, 2015)
The purpose of this article is to present mixed methodology evaluation data regarding a professional development initiative designed to offer non-certified special education teachers specialized classroom and teacher certification support. The project was grounded in evidence-based strategies that resulted in direct implications for teacher preparation, retention, and certification. To maximize benefits of participation in this project, access to instructional resources was provided. Participants benefitted from face-to-face communities of practice and a virtual learning environment designed to establish a shared culture of improvement and collaboration. Teacher participants generally felt factors such as "encouragement, motivation, and support they received from their colleagues contributed to their decision to pursue a special education teaching career." The evaluation findings informed a professional development model incorporating the essential components of professional development, learning communities, and mentorship. The findings further indicated that teacher professional development should specifically address instructional strategies, understanding of special educational issues, and skill attainment.